Essays in Labor Markets: Gender, Fertility and Education - Philip Rosenbaum (Copenhagen Business School (CBS), 2019)
This Ph.D. thesis, titled Essays in Labor Markets – Gender, Fertility and Education, analyzes different economic problems within the field of labor economics. It consists of three independent research papers that can be read separately. Although the topic in each chapter is different, they have common ground in the empirical methods applied. The first chapter of this thesis, Does Early Childbearing Matter? New Approach Using Danish Register Data, studies how women's timing of fertility affects their long-term labor market outcomes. This paper is currently resubmitted to the academic journal Labour Economics.
hdl:10398/9714
Keywords: 650